THE DIFFERENCE CHANGES IN WEIGHT IN THE DOTING MOTHER AND EXCLUSIVE BREASTFEEDING DOES NOT SUCKLE (Study in Ngudirejo Village, Diwek, Jombang) - . Nurhalima; . Ruliati; Nita Arisanti Y (STIKES Insan Cendekia Medika Jombang, 2012)
One of the benefits of granting exclusive breastfeeding is still in the controversy is to reduce the weinght of anursing mother. This is because of the production of milk the mother needs a lot of energy about 500 kcal perday. This research aims to understand the difference changes in weight the doting mother and does notsuckle exclusive breastfeeding in ngudirejo the village, the sub-district diwek, district jombang. Nalyticsurvey design research with cross sectional approach. The populasi all the mothers who had children agedmore than six months in the village ngudirejo kecamatan diwek kabupaten jombang a number of 52 people.Sampling using a purposive sampling. Sampelnya some women who have clidren aged more than 6 bulan inngudirejo village sub-district diwek district jombang a number of 46. Variabel independennya nursingmother breast-fed exclusively and not exclusively and variable dependennya the difference changes inweight. The collection of data using a questionnaire and observation. Data processing using editing, as well,scoring, tabulating and data analysis using mann-whitney. The research results obtained that majority ofrespondents giving mother BREAST MILK is not exclusive 23 respondents that her weight up. While motherswho provide exclusive BREAST MILK as much as 23 respondents i.e. consists of 19 (82.6%) of respondentsthat weight down, 3 (13,0%) of respondents who fixed weight, as much as 1 (4,3%) of respondents whoseweight is up. With analysis of data using mann-whitney ρ = 0,000 signnificance in value. Then h1 accepted.That there are differences changes in weight on the doting mother breast-fed exclusively and not exclusivengudirejo village, sub-district diwek, district jombang.